MALE DANCERS OF SABAR-STARS OF A FEMALE TRADITION - Seye, Elina (International Library of African Music, 2016)
This article discusses the role of male dancers within the Senegalese sabar tradition. The most common context for sabar dancing is social dance events that are dominated by non-professional female dancers. However, since the independence of Senegal in 1960 sabar dancing has also been developed as a stage art in folkloric dance companies known as ballets in West Africa. Later sabar also began to be performed by dancers and dance groups on stage with mbalax bands. Both of these newer forms of sabar dancing take the form of pre-planned choreographies performed by both male and female dancers; but, many of the best known sabar dancers today are men. Developments caused by the professionalisation of sabar dancing and analyses of the changes that have occurred in the style of dancing to emphasise the masculinity of the male dancers as opposed to the ideas of femininity traditionally attached to sabar dancing are discussed.
Keywords: African Music